Functional Mechanisms and Clinical Translation of Resveratrol for Lung Cancer Intervention - Chenxi Yang (Theoretical and Natural Science, 2026)
Lung cancer patients commonly suffer from tumor immune escape and acquired chemotherapy resistance, and conventional comprehensive treatment schemes still have prominent clinical limitations. Resveratrol, a low-toxicity natural polyphenol, has become a key research focus for adjuvant lung cancer therapy. This paper systematically reviews the anti-lung-cancer mechanisms of resveratrol, relevant epidemiological evidence, and bottlenecks hindering its clinical translation. Resveratrol remodels macrophages to secrete interleukin-18 (IL-18) and subsequently activate CD8+T cells; it blocks the STAT3/HIF-1α/VEGF signalling cascade to suppress tumour angiogenesis and hinders the TLR4/NLRP3 inflammatory axis to mitigate immunosuppressive tumour microenvironments. Moreover, resveratrol upregulates microRNA-506 to repress sphingosine kinase 1 (SPHK1), arresting tumour cell cycle progression and triggering apoptosis, and it reverses chemotherapy resistance in lung cancer through multiple synergistic pathways. Population-based studies have confirmed that dietary resveratrol intake correlates with a reduced risk of lung cancer onset. Nevertheless, several obstacles remain, including low bioavailability of resveratrol, a scarcity of lung cancer-specific clinical trials, and ongoing debates over standardized dosing regimens. This paper integrates current research findings to provide theoretical support for the development of optimized nanoformulations and combinatorial adjuvant therapeutic strategies for lung cancer.